BioDramatics - Crossroads in Science & Theater in the Creation of Luminesce: A BioDramatic Fiction. - Napier, Wally A. (Tufts Archival Research Center, 2016)
Biology, being the study of life, and Drama, being the study of human interaction, are intimately connected at their cores. Our biology determines our being, and our humanity sculpts biology in its study, practice, and form. These points of intersection between Biology, Theater, and Media/Communications cumulatively form a discipline of academic study I have identified as — BioDramatics. The nature of BioDramatics is fivefold: Dramaturgical, Communicative, SocioPolitical, Scientific and Theatrical. Through the one lens of BioDramatics, however, one is able to grasp the interconnectivity of these subjects in their entirety. Unfortunately, this unique union — the relationship between Science and Art — is often taken for granted, or ignored entirely as the byproduct of three apparently separate academic entities; Biology, Drama, and Communications. We instead form the illusions that audiences and actors don't care about science, and that scientific research is free from emotion and humanity. Such beliefs are seriously damaging to these fields of work because such separation of academic study inhibits cross-discipline discussion, and obscures the profound and practical insights that rest along the line where the biological meets with the artistic. Further, these damaging beliefs are propagated when biological science is either poorly or inaccurately communicated. The following paper is supported with documentation from scientific literature, quotes from dramatic works, and notes from personal experiences playwriting and directing, including my writing and staging of my thesis production Luminesce: A BioDramatic Fiction, with the hope of outlining the concepts and nature of BioDramatics and describing how it remedies the disconnects recognized above.